New fire alarm and smoke detector sensor using CCTV - Siti Norhafiza, Othman (2012)
In electrical engineering field, image processing is any form of signal processing. For mostly the input is a photograph, which is in picture or video frame; while the output of image processing can be either an image or a set of characteristics or a parameter that related to the image. Most of the time image processing refers to digital image processing however optical and analog image processing also available. On the other hand, computer vision definition is the science and technology of machines that it can see, where see in this case means that the machine is able to extract information from an image that is necessary to solve some information. The main purpose of this study is to design system that capable to detect smoke and fire using the CCTV. Image analysis was done using software MATLAB until get desired output.